2018
DOI: 10.1080/00275514.2018.1442078
|View full text |Cite
|
Sign up to set email alerts
|

Using collections data to infer biogeographic, environmental, and host structure in communities of endophytic fungi

Abstract: Biodiversity collections contain a wealth of information encapsulated both in specimens and in their metadata, providing the foundation for diverse studies in fields such as ecology. Yet biodiversity repositories can present a challenge for ecological inferences because collections rarely are structured with ecological questions in mind: collections may be opportunistic in space or time, may focus on particular taxonomic groups, may reflect different collection strategies in different places or times, or may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…If coevolution or codivergence has occurred between hosts and their endophytes, then unusual endophytic taxa could occur in hosts from remote portions of the plant phylogeny (Hassani et al ., ). Non‐vascular plants, in particular, deserve more attention, as these plants have different evolutionary histories, physiology, growth habits and preferred habitats than vascular plants (Huang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…If coevolution or codivergence has occurred between hosts and their endophytes, then unusual endophytic taxa could occur in hosts from remote portions of the plant phylogeny (Hassani et al ., ). Non‐vascular plants, in particular, deserve more attention, as these plants have different evolutionary histories, physiology, growth habits and preferred habitats than vascular plants (Huang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…To best share information among vouchers, standardized protocols (such as drying time and temperature) could be helpful to adopt, though we acknowledge the challenge of implementing such standards during field collection. Deposited cultures could provide many of the same benefits as host vouchers, but would also allow researchers to grow endophytes of interest to meet various experimental goals (Huang et al ., ; Suryanarayanan, ). Finally, the plant taxonomy is ever‐changing, thus as future researchers interpret published work, they may wish to examine accessions to determine the most current taxonomic placement of the focal host or endophyte.…”
Section: Discussionmentioning
confidence: 99%
“…Reductionist experiments facilitate mechanistic studies to elucidate the underlying biology of a system, rendering culture collections an important translational research tool to bridge big HTS data sets with biologically relevant activities. These resources enable critical inquiries into specific microbial interactions, such as linking functional phenotypes like pathogen suppression to specific microbiome constituents and their respective bioactive chemistries (53). For this study, we designed a pipeline that allowed us to assign taxonomy to bulk cultures obtained from citrus tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, examination of the literature revealed that a wide range of fungi often occur as endophytes, including lichenicolous fungi (Huang et al 2018, Moler and Aho 2018, Voglmayr et al 2019) and insect pathogens (Razinger et al 2018, Rondot andReineke 2018). We expect that the kinds of fungi known to occur as endophytes will only increase as more NGS studies are published.…”
Section: Species Compositionmentioning
confidence: 97%